Cataloguing without tears : Managing knowledge in the information society - Read, Jane.; Czajkowski, Adrian; ScienceDirect eBooks (Oxford [England] : Chandos Publications, 2003)
This book is an introduction, 'handy' and authoritative guide to the principles of cataloguing for librarians, information scientists and information managers. It is intended to be used in conjunction with an internationally recognised standard to show how, firstly, cataloguing underpins all the other activities of an information service and, secondly, how to apply best practice in a variety of different situations.
Part 1. The big picture: 1. Why bother to catalogue? -- 2. What to catalogue -- 3. Who should catalogue -- 4. How to catalogue ... and not reinvent the wheel -- Part 2. The nitty gritty: 5. Is it a book is it a journal? -- 6. What's a strange attractor? Cataloguing subjects you know nothing about. -- 7. Ici on ne lit pas le francais: unknown languages and how to deal with them -- 8. Special cases.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Elsevier
Keywords: Cataloging; Library administration; Catalogage; Bibliothèques -- Administration; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General; Cataloging; Library administration; Catalogisering; Titelbeschrijving; Onderwerpsontsluiting; Electronic books